Copyright Law In Palestine: An Overview - Mohammed M.M Qtait; Haliza A Shukor; Intan Nadia Ghulam Khan (Penerbit USIM, Universiti Sains Islam Malaysia, 2024)
Copyright protection in Palestine is under the Palestinian Copyright Act 1911 (Act 45) and Arab Copyright Convention 1981. The Palestinian Copyright Act 1911 has not been amended since enacted in 1911. This causes a lack of protection of copyright works in the digital environment. Hence, this paper aims to identify and explain the provisions contained in the Palestinian Copyright Act 1911 (Act 45) related to the digital area and highlight issues related to it. This paper concludes that there are issues related to copyright in the digital environment in Palestine which requires regulation by the Palestinian Copyright Act 1911.